Prevalence of viral co-infection among COVID-19 cases in association disease severity and oral hygiene - Adham, Zeina S; Al-Ghurabi, Batool H (Journal of Baghdad College of Dentistry, 2021)
Background: In December 2019, an episode of COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV2) was reported in Wuhan, China and has spread around the world, increasing the number of contagions. Cytomegalovirus (CMV) and Epstein-Barr virus (EBV) are common herpesviruses that can cause persistent latent infections and affect the developing immune system.The study was conducted to explore the prevalence and reactivation of CMV and EBV antibodies in COVID-19 patients group in comparison to healthy group and to investigate the association between the presence of these viruses with each of severity of disease and oral hygiene. Materials and Methods: Eighty Five subjects were participated in this case control study (50 patients with COVID-19 and 35 healthy controls), their age range from 18 to 77 years. Oral health status was established by oral hygiene index. Serum obtained from patients and controls was analyzed using ELISA to assess levels of anti- CMV and anti- EBV antibodies. Results: The study revealed that the mean of anti-EBV IgG in patients was significantly elevated (p<0.01) than that in controls. Otherwise, there was no significant difference (p>0.05) in levels of anti- EBV IgM, anti- CMV IgG and IgM between two groups (P>0.05). In addition there were no significant differences between patients and controls (p>0.05) in the number and percentage of anti-EBV and anti-CMV antibodies. Interestingly, there was a significant increase in the level of anti-CMV IgM in severe cases as compared to mild cases, (P<0.01). Furthermore, these results revealed that there were no significant differences (P>0.05) in levels of anti-viral antibodies in patients with good oral hygiene compared to patients with poor oral hygiene. Conclusions: Higher frequency of anti-EBV IgG among patients indicates that latent infection is more common in COVID-19 patients. While an increased percentage of anti-CMV IgM indicated reactivation of latent infection and is related to disease severity suggesting that COVID-19 can cause cellular immune impairment.